Translational fusion hybrid Bt genes confer resistance against yellow stem borer in transgenic elite Vietnamese rice (Oryza sativa L.) cultivars - Ho, N.H.; Baisakh, N.; Oliva, N.; Datta, K.; Frutos, R.; Datta, S.K. (Wiley, 2006)
We have shown the efficacies of translationally fused gene (cry1Ab‐1B) under the control of maize ubiquitin promoter and hybrid Bt gene (cry1A/cry1Ac) driven by rice Actin‐1 promoter against the yellow stem borer (Scirpophaga incertulas Walker, YSB) insect in rice (Oryza sativa L.). The integration, expression, and functionality of the transgenes were confirmed by Southern, western, and insect bioassay. The bioassay results correlated with the molecular data. The amount of Bt protein (within the range of 0.8–1.3% of the total soluble protein) in the transgenics was sufficient to cause 100% mortality of the neonate larvae of YSB within 1 wk of infestation. The transgenic plants expressing the foreign Bt protein were normal in phenotype with as good seed setting as the nontransgenic control plants.